Sous les yeux de l’Occident : recherches féministes et discours coloniaux - Mohanty, Chandra Talpade (Genre, postcolonialisme et diversité de mouvements de femmes, 2010)
Keywords: EDI; afro-féminisme; approches et analyses; cours; discipline; discours dominant; droits des femmes*; ethnocentrisme; féminisme africain; féminisme autochtone; féminisme du sud; féminisme décolonial; féminisme transnational; histoire et politique; injustices épistémiques; inégalités; justice sociale; militance; patriarcat; phi4336; philosophie politique; pol4212; pratiques féministes; premier cycle; privilèges; racisme; sciences humaines; sociologie; sujet du féminisme; système colonial; systèmes d'oppressions; thématiques; théorie féministe; violences

Queer Theory and Native Studies: The Heteronormativity of Settler Colonialism - Smith, A. (GLQ -NEW YORK-, 2010)
Queer studies highlights the importance of developing analyses that go beyond identity and representational politics. For Native studies in particular, queer theory points to the possibility of going beyond representing the voices of Native peoples, a project that can quickly become co-opted into providing Native commodities for consumption in the multicultural academic-industrial complex. The subjectless critique of queer theory can assist Native studies in critically interrogating how it could unwittingly re-create colonial hierarchies even within projects of decolonization. This critique also sheds light on how Native peoples function within the colonial imaginary-including the colonial imaginary of scholars and movements that claim to be radical. At the same time, Native studies can build on queer of color critique's engagement with subjectless critique. In the move to go "postidentity," queer theory often reinstantiates a white supremacist, settler colonialism by disappearing the indigenous peoples colonized in this land who become the foils for the emergence of postcolonial, postmodern, diasporic, and queer subjects. With respect to Native studies, even queer of color critique does not necessarily mark how identities are shaped by settler colonialism. Thus a conversation between Native studies and queer theory is important, because the logics of settler colonialism and decolonization must be queered in order to properly speak to the genocidal present that not only continues to disappear indigenous peoples but reinforces the structures of white supremacy, settler colonialism, and heteropatriarchy that affect all peoples.
Keywords: amériques; approches et analyses; colonialisme; communication; cours; discipline; féminisme autochtone; féminisme décolonial; histoire et politique; militance; premier cycle; queer; régions géographiques; sciences humaines; soc2014; suprématie blanche; système colonial; systèmes d'oppressions; thématiques; violences; études autochtones; études culturelles

Indigenous women and feminism: politics, activism, culture - Suzack, Cheryl; Huhndorf, Shari M.; Perreault, Jeanne; Barman, Jean (Women and indigenous studies series, 2010)
"Can the specific concerns of Indigenous women be addressed within current mainstream feminist and post-colonial discussions? Indigenous Women and Feminism: Politics, Activism, Culture proposes that a dynamic new line of inquiry -- Indigenous feminism -- is necessary to truly engage with the crucial issues of cultural identity, nationalism, and decolonization particular to Indigenous contexts. Through the lenses of politics, activism, and culture, this wide-ranging collection examines the historical roles of Indigenous women, their intellectual and activist work, and the relevance of contemporary literature, art, and performance for an emerging Indigenous feminist project. The questions at the heart of these essays -- What is at stake in conceptualizing Indigenous feminism? How does feminism relate to Indigenous claims to land and sovereignty? What lessons can we learn from the past? How do Indigenous women engage ongoing violence and social and political marginalization? -- cross disciplinary, national, academic, and activist boundaries to explore in depth the unique political and social positions of Indigenous women."--Page 4 de la couverture."A vital and sophisticated discussion that will change the way we think about modern feminism, Indigenous Women and Feminism will be invaluable to scholars, activists, artists, community organizers, and those concerned with Indigenous and feminist issues at home and abroad."-- Résumé de l'éditeur.
Keywords: activisme; approches et analyses; arts; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; militance; pol4105; premier cycle; premières nations; système colonial; systèmes d'oppressions; territoire; thématiques; études autochtones; études féministes; études littéraires